Students’ Perception Toward the Utilization of Tiktok as Vocabulary Learning Media - Mikhael Parlindungan Hutasoit; Margana; Yuyun Yulia; Hillario Satria (Postgraduate, University of Mataram, 2025)
TikTok videos serve as a prevalent method for augmenting vocabulary acquisition. This study aims to describe students' perceptions and motivation toward the role of TikTok in increasing vocabulary. This study employs a qualitative research method. The subjects of this study were students from SMA Sang Timur Yogyakarta during the academic years 2024 and 2025. The interview questions were adapted from interview questions developed by Anumathan & Hashim (2022). The results of the study TikTok videos are considered a good medium for increasing students' vocabulary and can be a supporting medium for teachers to teach with unique content and methods. In addition, students enjoy using TikTok as a learning medium because of its various interesting videos, features, and filters. However, students think that TikTok cannot be employed as the main media for acquiring vocabulary, other sources are still needed to increase vocabulary more rapidly. It can be summarized that students consider the utilization of TikTok can increase their vocabulary. Also, with TikTok, students agree that they have more fun exploring vocabulary both as viewers and content creators.